Salem College May Day, 1960. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 5-8-60 p.1C. Oversize.
Salem College May Day, 1960.The women are: Sally Wood,Anita Hatcher,Suzanne Drake,Beverly Wollny,Dot Grayson,Carolyn McLoud,Ida Mae Jennings,Vickie Van Liere,Lou Scales,Sally Townsend (May Queen),Jette Seear,Evelyn Vincent,Gay Austin,and Lou Adams.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth